Human security in East Asia [ challenges for collaborative action - Peou, Sorpong (Routledge security in Asia Pacific series, 2009)
This book explores human security in East Asia, focusing especially on the challenges of coordination and collaboration among actors involved in securing and promoting human security. It includes detailed case studies of military interventions in East Asia, including East Timor, and also non-military interventions, including international criminal justice in Cambodia.